2015
DOI: 10.1080/19648189.2015.1056384
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of fracture initiation and propagation using a tri-axial hydraulic fracturing test system in naturally fractured reservoirs

Abstract: A series of laboratory hydraulic fracture experiments was conducted on synthetic rock samples to investigate the mechanism of hydraulic fracture initiation and propagation of a pressurised wellbore in non-fractured and fractured reservoirs. To achieve this goal, the influence of pre-existing fracture (both on and far from the wellbore wall) and horizontal differential stress was investigated on the fracture initiation and propagation in different stress regimes. In reservoirs with no fracture due to the high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…With the propagation of the hydraulic fractures, a main fracture is formed perpendicularly to the direction of the minimum principal stress. Moreover, the greater the horizontal principal stress difference is, the more easily the main straight hydraulic fracture will form . The results of in‐situ stress tests of the No.…”
Section: Morphology Of Hydraulic Fractures and Prediction Model Of Pomentioning
confidence: 99%
“…With the propagation of the hydraulic fractures, a main fracture is formed perpendicularly to the direction of the minimum principal stress. Moreover, the greater the horizontal principal stress difference is, the more easily the main straight hydraulic fracture will form . The results of in‐situ stress tests of the No.…”
Section: Morphology Of Hydraulic Fractures and Prediction Model Of Pomentioning
confidence: 99%
“…NFs and BPs may cause hydraulic fractures to extend along or through the structure surfaces [11,17,18]. Various forms of HF in conditions of different confining pressures, NFs, and crustal stress fields as well as the best boundary conditions for the production of many fracturing cracks have also been investigated [19][20][21]. The extension rule of HF after intersecting with NFs has been very clear [22][23][24][25], but when making contact with BPs of different bedding angles, the extension rule will be more complicated [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Warpinski et al [5,6] found that the growth and geometry of hydraulic fractures were affected by the stress, joints, faults, interfaces and layer material property. Much research has studied factors affecting HF with the development of laboratory equipment and construction of True-Triaxial test devices [7][8][9][10][11][12]. Zhou et al [7] also studied the interaction between HF and NF through a series of experiments and presented the crossed boundary based on different stress regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Sarmadivaleh et al [8] investigated the influences of interface cohesion and approach angle on the interaction between NF and HF. Dehghan et al [9,10] studied the effect of dip direction of NF on HF propagation as well as stress state and approach angle. Guo et al [11] studied several factors including the type of injecting fracturing fluids, pump flow rate, fracturing pressure curve characteristics, and fracture morphology.…”
Section: Introductionmentioning
confidence: 99%